Tobacco Transcription Factor NtbHLH123 Confers Tolerance to Cold Stress by Regulating the NtCBF Pathway and Reactive Oxygen Species Homeostasis - Zhao, Qiang; Xiang, Xiaohua; Liu, Dan; Yang, Aiguo; Wang, Yuanying (Frontiers in plant science, 2018)
Cold stress is a major environmental factor that impairs plant growth and development, geographic distribution, and crop productivity. The C-repeat binding factor (CBF) regulatory pathway has an essential role in response to cold stress. Here, we characterized a bHLH transcription factor from , , in response to cold stress (4°C). Overexpression of enhanced cold tolerance in transgenic tobacco plants. Based on yeast one-hybrid, chromatin immunoprecipitation PCR, and transient expression analysis assays, binds directly to the G-box/E-box motifs in the promoter of the genes and positively regulates their expression. Furthermore, -overexpressing plants showed lower electrolyte leakage, reduced malondialdehyde contents, H O and reactive oxygen species (ROS) accumulation under cold stress, which contributed to alleviating oxidative damage to the cell membrane after cold stress treatment. And increased stress tolerance by improving the expression of a number of abiotic stress-responsive genes to mediate the ROS scavenging ability and other stress tolerance pathways. Taken together, we present a model suggesting that is a transcriptional activator that functions as a positive regulator of cold tolerance by activating , ROS scavenging-related, and stress-responsive genes.